PENGARUH ARTIS KOREA DALAM MENINGKATKAN BRAND IMAGE DAN PERILAKU KONSUMTIF MASYARAKAT [STUDI KASUS: BUKALAPAK] - Friska Lerinsa; Moch. Bagja Abdzul Azis; Putri Ayu; Syamsudin (Marketgram Journal, 2023)
The background of this journal research is the Korean wave phenomenon which is currently developing in Indonesia, many local brands or companies use Korean artists as advertisement stars or brand ambassadors, as was done by Bukalapak. The following will explain the impact that will occur on the behavior of Indonesian people when e-commerce increases the brand image of its products. With the aim that the Indonesian people can understand or take advantage of this e-commerce as a profitable medium. The method used is literature study from various national scale research journals. The data needed in this journal research was collected by means of literature studies, through print and electronic media. The results of this journal's research are the existence of the Korean Wave and the use of Korean artists as brand ambassadors influencing people's behavior in Indonesia. The positive impacts include being able to inspire fashion, how to dress and even increase product sales and the negative impacts include causing a cultural shift in Indonesia, wasting time and money buying products related to Korean culture.